Simultaneous Solubility Analysis of Paracetamol, Propyphenazone, and Caffeine Using Principal Component and Absorbance Ratio Regression Methods - Rosaldi, Hikmah; Pulungan, Ainil Fithri; Ridwanto, Ridwanto; Daulay, Anny Sartika (Pustaka Media Publishing, 2023)
Medicines can cause changes in the physiology or psychology of an organism when consumed. In general, medicines consist of several mixtures of active ingredients such as paracetamol (PCT), propifenazone (PRO), and caffeine (KAF), which are often found in several types of branded medicines that are claimed to be able to cure or treat. This research aims to obtain a type of solvent that has the smallest photometric error value and can completely dissolve the active ingredient mixture of PCT, PRO, and KAF. In general, organic solvents such as ethanol and methanol are very often used to dissolve compounds that mix with each other, but these solvents cannot always dissolve other active substances. Therefore, researchers carried out an analysis of several types of solvents that could dissolve the three active ingredients. Solvents that can dissolve perfectly without any specification stage must go through a solvent optimization process. The types of solvents that will be tested are methanol, HCl 0.1N, phosphate buffer pH 7.2, and the ratio of phosphate buffer: methanol (DM) (DM 9:1 pH 7.4), (DM 7:3 pH 7.8), (DM 5:5 pH 8.3), (DM 3:7 pH 8.9), and (DM 1:9 pH 9.6). The results of this research show that the solvent that has the smallest photometric error value and can completely dissolve the three active substances is the DM 7:3 pH 7.8 solvent with a total percentage of 0.0846%, which is the smallest value compared to other solvents that have been optimized.